An effective selective catalytic reduction catalyst contains oxygen bridge for NOx reduction based on low concentration of C3H6 at medium‐low temperatures. (8th May 2022) - Liu, Fang; Hu, Yiling; Liu, Guangli; Liu, Qing; Tang, Zhonghua; Yang, Li
Summary: Ammonia slip in NH3 ‐SCR will lead to the formation of viscous salt, which may block the downward heat exchangers, which is particularly serious in oil refinery stations. Oil refinery stations are usually rich in low concentration propane (C3 H6 ), and C3 H6 ‐SCR is considered to be a very promising NOx emission reduction technology. This study reported an effective NOx reduction catalyst based on low concentration C3 H6 at medium‐low temperature. CeO2 was used to optimize the catalyst, but instead of doping CeO2 to active component, and it was found that doping CeO2 on TiO2 to produce Ce‐Ti synthetic support was effective. This study elucidates that in refinery tail gas environment, a 5 wt.% Mn loaded on Ce‐Ti support catalyst (Mn5 ‐Ce/TiO2 ) can achieve 70% NO conversion, meanwhile the N2 selectivity is 100%. In order to explore the mechanism of activity enhancement, the catalysts were characterized before and after reaction. The results indicate that the addition of CeO2 provided more acid sites for the adsorption of propene, and the structure and properties of Mn5 ‐Ce/TiO2 hardly changed after reaction, which helped to maintain high activity in de‐NOx process. The oxidation of Ce 3+ to Ce 4+, and the reduction of Mn 3+ to Mn 2+ promoted the reduction of NO, while the oxygen bridge Ce‐O‐Ti promoted the stability of the catalyst, so as to achieve a high conversion of NO.